Investigation of nuclear reactions in d + t system - O. O. Belyuskina; S. V. Berdnichenko; V. I. Grantsev; V. O. Grashilin; M. I. Doronin; T. I. Kibkalo; K. K. Kisurin; V. O. Kisurin; O. V. Kovalenko; M. F. Kolomiets; A. L. Lytvynsky; I. O. Mazny; et al. (Ядерна фізика та енергетика)
The results of measurement of inclusive of protons, deuterons and 3He spectra in the range 16° ≤ θL.C. ≤ 67.4° formed in the process of interaction of nuclei of deuterium and tritium are presented. Characteristic features of proton energy spectrum are described owing to the account of 4H sequential decay and final state interaction of a singlet neutron-proton pair processes. The account in the 3H(d, 3He)nn reaction of processes of final state two neutron interaction and successive decay through 4He* (Ex = 21.2, Γ = 0.7 MeV) resonance amplitude and Watson - Migdal amplitude allowed to describe the 3He nucleus spectrum shape. Experimental differential cross sections of elastic deuteron scattering on Tritium were obtained. The experiment was carried out on U-240 INR cyclotron with deuteron beam energy of 36.9 MeV. Energy spectra of protons and 3He-particles were studied.